Fragilidade ambiental : subsídios para a gestão de uso e ocupação do solo nas bacias hidrográficas periurbanas de Marechal Cândido Rondon-PR - Fruet, Jaqueline Gorisch Wilkomm (2016)
The Watersheds are used as geographical studies units that are intended monitoring, analysis and containment of environmental problems. Guided by the "natural potential frailty model" presented by Ross (1994, 1996), it was made the diagnosis of environmental fragility in seven (07) periurban watersheds of the city of Marechal Cândido Rondon, which are part of the Paraná Basin III, belonging the State of Paraná Western region. The preparation of letters of potential and emerging fragility, generated from the interpolation of the use of maps and land use, slope and soil type, allowed diagnose different degrees of environmental fragility potential and emerging basins. The objective was to contribute to the knowledge of the organization and distribution of soils in the landscape, according to their weaknesses in order to assist in the use and occupation process. The analysis of social and environmental factors that interrelate these landscape units showed that sectors with lower potential environmental fragility (very weak / weak) are the medium to high side, convex and divergent, with slope classes between 0 and 6% under the rule of Red Latosol. Areas with environmental average potential fragility occupy sectors with slope classes between 6 and 12%, with the presence of Red Nitosol, and strands of convergent-concave shapes, especially in the basins of streams and Butterfly Apepú. To a lesser extent, potential fragility classes of strong and very strong commitment denote the environmental balance of the basins in the aspect of sectors with convergent-divergent-concave and convex forms, associated with slopes above 20% and shallow soils. As for the emerging environmental fragility, all the basins were classified as medium-strong, respecting the interaction between the analyzed attributes (slope, forms the slopes, slope and land use). It notes that the results can inform future research in periurban catchments Rondon, for example, the loss of soil, integrating research results with a view to planning and management of land use